Pendampingan Penggunaan Aplikasi Buku Warung sebagai Upaya Edukasi Transformasi Pencatatan Akuntansi Manual ke Digital pada Usaha Rumah Makan Prasmanan Emmy Saelan - Chris Dayanti Br. Ginting; Hariany Idris; Masdar Ryketeng; Ricky Setiawan; Andi Nurul Azisah (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2025)
This community service activity aims to improve the competence of Micro, Small, and Medium Enterprises (MSMEs) in implementing a digital-based bookkeeping system through the use of the BukuWarung application. The target partner is the Emmy Saelan Buffet Restaurant in Makassar City. This activity uses a participatory educational approach, which actively involves partners in every stage of implementation, including needs observation, socialization of the importance of digital bookkeeping, training on the use of the BukuWarung application, practical assistance, and evaluation of implementation results. The results of the activity show a significant increase in the ability of partners to carry out regular financial records, group transactions according to category, and prepare simple profit and loss reports. In addition to improving technical skills, this activity also succeeded in building awareness of financial literacy and the importance of separating personal finances from business finances. This activity is expected to become a model for sustainable assistance for other MSMEs in adopting digital technology as an instrument for improving financial governance that is adaptive to the digital economic transformation.